Assessment of sustainable design practices in the fashion industry: experiences of eight small sustainable design companies in the Northeastern and Southeastern United States. Issue 1 (2nd January 2016) - Lawless, Erin; Medvedev, Katalin
ABSTRACT: The primary purpose of this research was to gain an understanding of designers' knowledge of sustainability and investigate current practices in sustainable fashion design in order to discover what variables influence designers' decisions during the design and product development process of sustainable fashion apparel. Qualitative, descriptive research methods, including an open-ended research guide and in-depth interviews, were used. The study focused on sustainable fashion designers from small design companies in the Northeastern and Southeastern United States. The study discusses some of the variables that impact the implementation of sustainable fashion design practices, such as current industry practices and expectations, consumer knowledge and acceptance, sustainable sourcing, production, and distribution options, as well as sustainable design education. In addition, gaps in knowledge regarding various aspects of sustainability among self-proclaimed sustainable fashion designers are identified.